Research integrity guidelines in the academic environment: The context of Brazilian institutions with retracted publications in health and life sciences - Stavale, Rafaelly; Pupovac, Vanja; Ferreira, Graziani Izidoro; Guilhem, Dirce Bellezi (Frontiers in Research Metrics and Analytics, 2022)
Although research misconduct is responsible for most of retractions in health and life sciences of authors affiliated to Brazilian institutions, there are few studies evaluating retraction notices and research misconduct in the country. Comprehension of the form of research misconduct may share light on weaknesses and strengths of individual, organizational and structural factors toward the implementation of research integrity culture. This policy and practice review aims to access the available information of research integrity offices and guidelines from Brazilian funding institutions and universities involved with retracted publications in health and life science based on a previously published systematic review. Additionally, we summarize the available guidelines and policies for research integrity in the country. We searched for publicly available guidelines and offices for research integrity. Fifteen institutions were analyzed: five funding agencies and ten universities. Forty percent of the funding agencies promoted research locally, and 60% promoted research nationally. Considering the funding agencies with national activity, 66% had a commission for research integrity. Thirty percent of the universities has no official office of research integrity or any publicly available guidelines. Most of the institutions had retractions due to some form of research misconduct. Institutions from Brazil involved with retracted publications lack instruments to prevent, supervise, and sanction research misconduct. The institutions of the country have pieces of what should be a system to promote and sustain research integrity practices. Nevertheless, there is a positive movement of researchers engaging in the investigation of research integrity, the creation of policies and training. This study emphasizes the increasing influence of Brazil’s scientific collaboration and production globally, as well as the impact of retractions in medical sciences. In contrast, it addresses the need for clear research integrity policies to foster high-quality and trustworthy research.